Bibliotherapy-Based Counseling for Self-Confidence in Dyslexic Students - Maulana, Angga; Azizah, Nur (Papanda Publisher, 2025)
The aim of this study is to determine the effect of implementing guidance and counseling with bibliotherapy techniques on increasing the self-confidence of dyslexic children at SMP Negeri 4 Muara Ancalong. This research employed a quantitative approach with a pre-experimental method using a One Group Pre-Test–Post-Test Design. The study was conducted at SMP Negeri 4 Muara Ancalong, East Kutai Regency, East Kalimantan Province, involving four dyslexic students (n = 4) as participants. Research instruments included an interview guide and a questionnaire that had been tested for validity and reliability. Data were analyzed using a paired sample t-test. The results showed that the mean self-confidence score before the implementation of bibliotherapy-based guidance and counseling was 108.75, and increased to 137.00 after the intervention. The statistical analysis revealed a significant effect of the intervention on improving self-confidence in dyslexic students (p-value = 0.002, < 0.05), indicating a substantial positive change in their self-perception and learning motivation. However, the findings should be interpreted with caution due to the very small sample size (n = 4), which limits the generalizability of the results. Schools are encouraged to develop more adaptive guidance and counseling programs for students with special needs, including dyslexia. Providing dyslexia-friendly reading materials and training school counselors in bibliotherapy techniques can enhance intervention effectiveness. Furthermore, raising awareness among all educators about the importance of psychosocial support for students with learning disabilities is essential to foster a more inclusive and supportive school environment.